1988
DOI: 10.1002/ijc.2910420526
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of human hematopoietic cell lines for the propagation and characterization of HBLV (human herpesvirus 6)

Abstract: Details of the productive infection of established human cell lines of diverse origin by HBLV (also designated Human Herpesvirus 6) are described in this report. The infection and replication of HBLV in several T and B lymphoid and other cell lines was observed by electron microscopic examination, by the detection of viral antigen expression by indirect immunofluorescence assay (IFA) and by the presence of HBLV DNA by Southern blot hybridization. Several of these cell lines produced large amounts of virus. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
53
0
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(55 citation statements)
references
References 18 publications
(4 reference statements)
0
53
0
2
Order By: Relevance
“…[11][12][13][14][15] In the present report, we describe two cases of immunocompetent adults who presented with fever and generalized lymphadenopathy, and on biopsy were found to have viral lymphadenitis with massive numbers of viral inclusions in CD4-positive T lymphocytes. The presence of the virus in these cells was confirmed by immunohistochemistry, and electron microscopy and molecular studies identified distinctive features of HHV-6B.…”
mentioning
confidence: 74%
“…[11][12][13][14][15] In the present report, we describe two cases of immunocompetent adults who presented with fever and generalized lymphadenopathy, and on biopsy were found to have viral lymphadenitis with massive numbers of viral inclusions in CD4-positive T lymphocytes. The presence of the virus in these cells was confirmed by immunohistochemistry, and electron microscopy and molecular studies identified distinctive features of HHV-6B.…”
mentioning
confidence: 74%
“…Cultures were kept for three days and were pulsed with [methyl-3 H]thymidine (Amersham) at 1 Ci per well during the last 16 h of culture. Cells were then harvested with an automated cell harvester (Tomtec, Orange, Conn.), and [methyl- 3 H]thymidine incorporation was measured in a Microbeta Trilux counter (Wallac, Turku, Finland). A well or culture was defined as specific for the corresponding antigen when the counts per minute were greater than 1,500 and exceeded the reference counts per minute (in the absence of the antigen) by at least three times.…”
Section: Methodsmentioning
confidence: 99%
“…Only HHV-6B has been definitively proven to cause human disease (44,49). HHV-6 also has a neurotropic property (3) and was found to cause subacute leukoencephalitis, manifesting as MS and demyelination of the central nervous system (8,19). Epidemiologic studies have shown that the vast majority of primary HHV-6 infections occur within the first year of life (13,50).…”
mentioning
confidence: 99%
“…However, it is now well known that HHV-6 exhibits tropism mainly for T lymphocytes and monocytes/macrophages and that various kinds of cells, including myeloid precursor cells, megakaryocytes, natural killer cells, fibroblasts, astrocytes, and hepatoma cells, are also susceptible to HHV-6 infection (1,15,18,19,22). Various immunobiological alterations of T lymphocytes have been observed following infection with HHV-6.…”
mentioning
confidence: 99%